Análise da interface de união entre cimento resinoso auto-adesivo à dentina erodida in vitro - Moda, Mariana Dias [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Considering the significant increase of erosive lesions and the need for studies to evaluate the adhesion on a eroded substrate. The purpose of this study was to evaluate the bonding interface between self-adhesive resin cement to in vitro eroded dentin. Seventy-two third molars were used and divided into two groups: group 1 (sound dentin) and group 2 (eroded dentin). The in vitro erosion was created following a demineralization protocol, in which the specimens of group 2 were immersed in demineralizing solutions 2 minutes per cycle, and in remineralizing solution, 10 minutes per cycle, during 9 days. Both groups were submitted to four dentin surface treatments: control group (without any treatment), 2% chlorhexidine, 20% polyacrylic acid, and 0,1M EDTA pH 7.4 (n=9). TPH resin-based composite blocks were bonded with RelyX U200 self-adhesive resin cement on the pretreated dentin surfaces. The teeth were submitted to precision cutter, thus obtaining samples forms of sticks. The samples were submitted to microtensile bonding test to evaluate the bonding strength between selfadhesive resin cement to dentin, 24 hours and 8 months after the bonding procedure. The fractured samples were evaluated in scanning electron microscopy (SEM), to classify the fracture pattern of these interfaces. Finally, three specimens of each group were longitudinal cut and obtained three slices per group and evaluating by confocal laser scanning microscopy (CLSM), with the purpose to analyze qualitatively the dentin/cement interface. The results showed that the etched dentin showed significant increase in density and depth of resinous tags compared to sound dentin, although little difference in bond strength values has been found. Different types of treatments performed on dentin, in general, increased the bonding strength values compared to the control group. The storage of the samples in artificial saliva for 8 months, seems to have been not enough to cause significant degradation of the adhesive interface.

Considerando o expressivo aumento de lesões erosivas e a necessidade de estudos que avaliem a adesão sobre um substrato erodido. O propósito deste estudo foi avaliar a interface de união entre cimento resinoso auto-adesivo à dentina submetida à erosão in vitro. Setenta e dois terceiros molares humanos foram utilizados e divididos em dois grupos: grupo 1 (dentina normal) e grupo 2 (dentina erodida). Para a obtenção da erosão in vitro foi empregado um protocolo, no qual os espécimes ficaram imersos em solução desmineralizante , 2 minutos por ciclo, e em solução remineralizante , 10 minutos por ciclo, ao longo de 9 dias. Na sequência, ambos os grupos foram submetidos a quatro tratamentos de superfície dentinária: grupo controle (sem tratamento), clorexidina 2%, ácido poliacrílico 20%, e EDTA 0,1M (n=9), previamente ao processo de união. Blocos de resina composta TPH foram cimentados com cimento resinoso auto-adesivo RelyX U200 às superfícies dentinárias. Os dentes foram submetidos à cortadeira de precisão, onde obteve-se amostras em forma de palitos, os quais foram submetidos ao teste de microtração para avaliar a resistência de união entre o cimento resinoso e dentina, 24 horas e 8 meses após o procedimento de união. Associada a microtração, a análise do padrão de fratura dessas interfaces foi realizada em microscopia eletrônica de varredura (MEV). Em amostras distintas, foram obtidas fatias longitudinais dos dentes, sendo três espécimes de cada grupo, os quais foram avaliados em microscopia confocal (MC), para análise qualitativa da interface dentina/cimento. Os resultados mostraram que a dentina previamente erodida apresentou considerável aumento na densidade e profundidade de tags resinosos em relação à dentina normal para os diferentes grupos, embora pouca diferença nos valores de resistência de união tenha sido encontrada. Os diferentes tipos de tratamentos realizados em dentina, de uma forma geral, aumentaram os valores de resistência de união em comparação ao grupo controle. O armazenamento das amostras em saliva artificial por 8 meses, parece não ter sido suficiente para causar uma significativa degradação da interface adesiva.
Analysis of bonding interface between self-adhesive resin cement to in vitro eroded dentin
Keywords: Dental erosion; Dentin; Resin cement; Cimentos de resina; Dentina; Erosão dentária